PENGARUH BUDGET EMPHASIS, BUDAYA ORGANISASI, DAN KEJELASAN SASARAN ANGGARAN TERHADAP BUDGETARY SLACK (Studi pada SKPD Kabupaten Aceh Tamiang) - Ilham Safari; Afrah Junita; Tuti Meutia (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This study aims to determine the effect of Budget Emphasis, Organizational Culture and Clarity of Budget Targets on Budgetary Slack. This research was conducted at the SKPD of Aceh Tamiang Regency. The sample in this study amounted to 140 people. The sampling technique used purposive sampling, the sampling using certain criteria. This research is a quantitative research in the form of data in the form of numbers. The data source used is primary data. Data were obtained from distributing questionnaires to research respondents. The data analysis technique used multiple regression analysis assisted by the SPSS program. The results of the study partially show that Budget Emphasis and Organizational Culture have a significant effect on Budgetary Slack in the SKPD Aceh Tamiang. Clarity of Budget Targets has a negative and significant effect on Budgetary Slack in the SKPD Aceh Tamiang. Simultaneous Budget Emphasis, Organizational Culture, and Clarity of Budget Targets effect on Budgetary Slack in the SKPD Aceh Tamiang. The limitation of this research is that the sample is only taken from the parties participating in the preparation of the budget activity program, so that it does not represent it as a whole. In addition, in collecting data, researchers only use the questionnaire method, so they will not get answer that better reflect the actual situation. Suggestions for future researchers to expand this research by adding other variables. In addition, it is also expected to increase the number of respondents and use the interview method when collecting data.